An Electrochemical Study on the Effect of Metal Chelation and Reactive Oxygen Species on a Synthetic Neuromelanin Model - Xu, Ri; Soavi, Francesca; Santato, Clara (Frontiers in Bioengineering and Biotechnology, 2019)
Neuromelanin is present in the cathecolaminergic neuron cells of the substantia nigra and locus coeruleus of the midbrain of primates. Neuromelanin plays a role in Parkinson’ s disease (PD). Literature reports that neuromelanin features, among others, antioxidant properties by metal ion chelation and free radical scavenging. The pigment has been reported to have prooxidant properties too, in certain experimental conditions. We propose an explorative electrochemical study of the effect of the presence of metal ions and reactive oxygen species (ROS) on the cyclic voltammograms of a synthetic model of neuromelanin. Our work improves the current understanding on experimental conditions where neuromelanin plays an antioxidant or prooxidant behavior, thus possibly contributing to shed light on factors promoting the appearance of the PD.